Absolute Neutrophil Count in Diagnosis of Neonatal Sepsis : A Hospital Based Cross Sectional Study - Chowdhury, Rana; Barua, Tanuka; Dey, Dipika; Ullah, Monir; Dhali, Md Balayat Hossain; Chowdhury, Priyanka (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background : Sepsis is the leading cause of neonatal death in developing countries. Delay in initiating treatment can considerably increase the morbidity and mortality. So early diagnosis is important.Traditional methods such as blood culture do not provide a rapid diagnosis. Absolute neutrophil count is one of the important hematological markers for diagnosis of sepsis. The purpose of the study to see the absolute neutrophil count in diognosis of neonatal sepsis. Materials and methods: This is a hospital based cross sectional study conducted from January to June 2014. A total of 100 sick neonates admitted in the Neonatal ward of Chattagram Maa Shishu O General Hospital (CMSOGH) with suspected neonatal sepsis (Based on history and physical examination) constituted the study population. Investigation sent for Absolute neutrophil count, C-reactive Protein (CRP) and blood culture. The collected data was analyzed by statistical software packages SPSS method version 15. Results: A total of 100 sick neonates of both sexes with suspected sepsis were enrolled in this study, out of which most of the patient showed neutropenia (66%), C-reactive protein positive 65% and blood culture positive 33%. Within the Creactive protein positive patients 78.8% patient had neutropenia (c2 =17.711, p= .001). From blood culture positive patients 85% showed neutropenia (c2 =8.510, p= 0.014). Conclusion: Neutropenia is a common hematological finding in neonatal sepsis along with other screening test and neutropenia is more significant than neutrophilia. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 66-70